The coaching on lifestyle (CooL) intervention for obesity, a study protocol for an action-oriented mixed-methods study - Celeste E. van Rinsum; Sanne M. P. L. Gerards; Geert M. Rutten; Ien A. M. van de Goor; Stef P. J. Kremers (BMC, 2018)
Abstract Background Combined lifestyle interventions (CLIs) have proved to be effective in changing and maintaining behavioural lifestyle changes and reducing overweight and obesity, in clinical and real-world settings. In this CLI, lifestyle coaches are expected to promote lifestyle changes of participants regarding physical activity and diet. In the Coaching on Lifestyle (CooL) intervention, which takes a period of 8 to 10 months, lifestyle coaches counsel adults and children aged 4 years and older (and their parents) who are obese or are overweight with an increased risk of developing cardiovascular diseases or type II diabetes. In group and individual sessions, themes such as physical activity, dietary behaviours, sleep and stress are addressed. The aim of the present study is to monitor the implementation process of the CooL intervention and to examine how the lifestyle coaches contribute to a healthier lifestyle of the participants. Methods This action-oriented study involves monitoring the implementation process of the CooL intervention and examining the lifestyle changes achieved by participants over time, in a one-group pre-post design using mixed methods. Methods include semi-structured interviews, observations, document analysis, biomedical parameters and questionnaires. Discussion The added value of the CooL study lies in its action-oriented approach and the use of mixed methods, including both qualitative and quantitative research methods. The long-term coaching used in the CooL intervention is expected to have beneficial effects on sustained lifestyle changes. Trial registration NTR6208 ; date registered: 13-01-2017.